Optimasi Alat Muat dan Alat Angkut Untuk Meningkatkan Produksi Limestone Setelah Indarung VI Berproduksi Di PT Semen Padang - Marta Borisman; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Indarung VI factory began production in April 2017, causing an increase in the need forlimestone, which was sourced from the Existing Area, from 679,140 tons to 826,833 tons. This study aimsto find out whether production equipment in the existing area are able to meet these increased needs, anddetermine the optimization that must be done so that the needs are met. The approach taken is to make asimulation that describes the actual conditions (operating patterns, effective hours, productivity of tools) inthe field, to be compared with the production target. Optimization is done by analyzing the productivity ofproduction equipment and effective hours, compared with their theoretical productivity. After beingsimulated, it is known that the production equipment has an actual production capability of 679,140 tons,with a percentage of the production target of 82%. limestone. This means that production equipment has notmet the production target, so production equipment optimization must be done. Optimization carried out:Improved work efficiency Improved work efficiency from 58.97% to 82.65%, and redesigning matchingfleet. After the optimization above, the existing area production equipment has a total limestone productionof 840,111 tons per month, with a production achievement of 102%.Keywords: Optimization; Simulation; Effective Hours;Productivity;matching fleet